Real Time Detection Of Milk's Spoilage Using Au/go Bend Smf Sensor Based On Localized Surface Plasmon Resonance Effect - W. M. Mukhtar; I. Kamarolzaman (UMP Publisher, 2024)
JOURNAL OF MECHANICAL ENGINEERING AND SCIENCES (JMES)VOL.14, ISSUE4,7540–7550